Association of the awareness of the epidemic, mental health status with mobile phone screen use time in Chinese college students during COVID-19 isolation and control. - Min Fang; TengChi Ma; HongHong Li; Tuo Han; JiaJia Wang; ZhiLe Li; Jing Zhou (Public Library of Science (PLoS), 2023)
Objective This study aimed to investigate the awareness of the epidemic among college students and their mental health as well as to explore the association between their awareness of the epidemic mental health and the daily mobile phone screen use time, in order to provide guidance for the publicity of school epidemic prevention and control knowledge and the psychological counseling of students. Methods A cross-sectional design was employed among 780 college students, The Pandemic Fatigue Questionnaire, epidemic prevention and control knowledge and the mental health Scale were used to collect data through an online survey. Results 1. Awareness rate of the transmission routes and protective measures of COVID-19 among college students is higher when the daily mobile screen use time is 3-7 hours. 2. 21.79% of the 780 college students felt stressed; 24.87% felt anxious; 19.23% showed depression. 3. The scores of each subscale in the daily mobile phone screen use time of 3-7 hours and more than 7 hours were higher, and the scores of each subscale in the group of more than 7 hours were the highest. Further correlation analysis found that the time spent on mobile phone screens was positively correlated with stress, anxiety, and depression scores (r = 0.155, 0.180, 0.182, P<0.01). Conclusion During the COVID-19 isolation and control period, college students with different mobile screen usage time have different understandings of the epidemic. Long-term mobile screen use is related to the occurrence of psychological problems such as stress, anxiety, and depression. Therefore, education departments and schools should pay attention to college students' mobile phone use time to reduce the occurrence of bad psychological state of students.